Recruitment into psychiatry: a medical student perspective - Skuse, David (Int Psychiatry, 2005)
To ensure a successful future for our profession, we have to attract young enthusiastic doctors to take up residencies in psychiatry, but there have been murmurings of disquiet in recent years that we are not being as successful as we might, or as we should. We have taken soundings for the theme of this issue: why do too many medical students not consider psychiatry as a career choice? We bring together perspectives from around the globe: from Israel we have a contribution from Moshe Abramowitz and Daphne Bentov-Gofrit; from Guillem Pailhez and her colleagues we learn of a comparison between Spanish and US students; and from Australia we hear from Bruce Tonge.